(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
The samples of soil, leaves, and shoots of jute were collected from twenty spots of jute (variety BJRI-Tossa-8) fields from different locations in the Narail district of Bangladesh under AEZ-12 during the year 2022. The study intended to evaluate the soil’s physicochemical properties and nutrient concentrations in jute leaves and shoots of 120 days old plants (at the harvesting time of the plant). The soil pH was neutral to slightly alkaline (6.6 to 7.4), with organic matter content from 1.03 to 1.71%. Electrical conductivity was found non-saline which was 40 to 150 μS/cm at 0 to 15 cm depth. The dominant soil textural class was clay. The total N, P, and S in soils were found to be 0.21 to 0.31%, 0.027 to 0.0283% and 0.0002 to 0.0023%, respectively and available N, P, and S were found to be 0.0058 to 0.0087%, 0.0007 to 0.0018%, and 0.0001 to 0.0006%. The nutritional values of N, P, and S in leaves ranged from 3.00 to 11.75%, 0.2281 to 0.5627%, and 0.0056 to 0.0197%, respectively. The total N, P, and S concentrations in the shoots were 0.17 to 5.07%, 0.0012 to 0.2935%, and 0.0002 to 0.0011%, respectively. The study indicated that jute leaves are enriched in nutrition and may be a good source of nourishment for human health. This research also illustrated that the jute field had low to medium fertility soil status. It is suggested that the farmers of AEZ-12 should follow the fertilizer recommendation doses in jute cultivation for higher fiber yield and allow sufficient decomposition of jute roots and debris to sustain succeeding crop production and soil fertility. The study has given new information and guidelines for the researcher for future investigation. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 35-44